At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

Solve [tex][tex]$6x + c = k$[/tex][/tex] for [tex][tex]$x$[/tex][/tex].

A. [tex][tex]$x = \frac{k - c}{6}$[/tex][/tex]
B. [tex][tex]$x = 6(k + c)$[/tex][/tex]
C. [tex][tex]$x = 6(k - c)$[/tex][/tex]
D. [tex][tex]$x = \frac{k + c}{6}$[/tex][/tex]


Sagot :

To solve the equation [tex]\( 6x + c = k \)[/tex] for [tex]\( x \)[/tex], follow these steps:

1. Start with the given equation:
[tex]\[ 6x + c = k \][/tex]

2. To isolate the term containing [tex]\( x \)[/tex], subtract [tex]\( c \)[/tex] from both sides of the equation. This gives:
[tex]\[ 6x = k - c \][/tex]

3. Now, solve for [tex]\( x \)[/tex] by dividing both sides of the equation by 6:
[tex]\[ x = \frac{k - c}{6} \][/tex]

Thus, the solution to the equation [tex]\( 6x + c = k \)[/tex] for [tex]\( x \)[/tex] is:
[tex]\[ x = \frac{k - c}{6} \][/tex]

Therefore, the correct choice is:
A. [tex]\( x = \frac{k - c}{6} \)[/tex]